Volume 2B: Turbomachinery 2020
DOI: 10.1115/gt2020-16059
|View full text |Cite
|
Sign up to set email alerts
|

Exploring Topology Optimisation of High Pressure Turbine Blade Tips

Abstract: This work presents the aerodynamic topology optimisation of high pressure turbine rotor blade tips. Before carrying out the topology optimisation on the blade tip, some initial tip design studies were carried out. The winglet shape was optimised using two different design space setups and parameter limits. The optimum winglet design features the largest overhangs and in the case of unconstrained optimisation proved to have 1.40% greater aerodynamic efficiency. Secondly, a radial basis function based parametris… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 22 publications
0
1
0
Order By: Relevance
“…Because of overhangs, OTL flow has to travel further distance to leave the tip gap, causing lower mismatch angle with the main flow and mitigating the mixing losses [15]. Vincekovic et al [16] did an aerodynamic winglet optimisation which was later used as a basis for the tip topology optimisation. They found that combining winglet with topology free squealer tip considerable efficiency benefit can be achieved.…”
Section: Introductionmentioning
confidence: 99%
“…Because of overhangs, OTL flow has to travel further distance to leave the tip gap, causing lower mismatch angle with the main flow and mitigating the mixing losses [15]. Vincekovic et al [16] did an aerodynamic winglet optimisation which was later used as a basis for the tip topology optimisation. They found that combining winglet with topology free squealer tip considerable efficiency benefit can be achieved.…”
Section: Introductionmentioning
confidence: 99%